A New Witness to the Gospel of Pseudo-Matthew : A Sermon in Vercelli, Biblioteca Capitolare LXXIII - Hawk, Brandon W. (Sacris erudiri, 2020)
This article presents a study of a witness to the Gospel of Pseudo-Matthew in Vercelli, Biblioteca Capitolare LXXIII, which has not previously been identified in scholarship on the apocryphon. This manuscript brings the total number of surviving, identified witnesses to 198. Even more, because the text of Pseudo-Matthew in Vercelli LXXIII is part of the P1a textual branch of witnesses, this identification allows for a reconsideration of the textual affinities of this branch and the transmission of the apocryphon for preaching in the Middle Ages. The article includes a description of the manuscript, discussion of related witnesses, and a detailed analysis of the text in relation to other witnesses to Pseudo-Matthew. This new witness to Pseudo-Matthew in Vercelli LXXIII further offers an opportunity to reassess the textual developments and transmission of this apocryphon specifically as a preaching text.